2004
DOI: 10.1016/j.ejphar.2004.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying diabetes enhancement of endothelin-1-induced contraction in rabbit basilar artery

Abstract: The influence of alloxan-induced diabetes on the reactivity of rabbit basilar artery to endothelin-1 was examined. Endothelin-1 induced concentration-dependent contraction of basilar arteries that was higher in diabetic than in control rabbits. Endothelium removal produced a higher enhancement of the endothelin-1-induced contraction in control than in diabetic rabbits. , enhanced endothelin-1-induced contraction in control rabbits and decreased the potency of endothelin-1 in diabetic rabbits. Sodium nitropruss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Unexpectedly, a higher-dose blockade of the ET B receptor also produced a rightward shift of the dose-response curve in a manner similar to ET A blockade. Previous studies in diabetic rabbit and rat basilar arteries have produced similar results using in vitro inhibition of ET B receptors (1,31,33). Interestingly, Matsumoto et al (33) showed that endothelial denudation of the diabetic basilar artery produced a significant leftward shift of the ET-1 dose-response curve.…”
Section: ) and Magnitude (R Max ) Of Vascular Responses To Et-1 And Amentioning
confidence: 58%
See 2 more Smart Citations
“…Unexpectedly, a higher-dose blockade of the ET B receptor also produced a rightward shift of the dose-response curve in a manner similar to ET A blockade. Previous studies in diabetic rabbit and rat basilar arteries have produced similar results using in vitro inhibition of ET B receptors (1,31,33). Interestingly, Matsumoto et al (33) showed that endothelial denudation of the diabetic basilar artery produced a significant leftward shift of the ET-1 dose-response curve.…”
Section: ) and Magnitude (R Max ) Of Vascular Responses To Et-1 And Amentioning
confidence: 58%
“…First, we examined reactivity of the basilar artery to ET-1 in all groups and to 5-HT only vehicle-treated control and GK rats but not in ET receptor antagonist treatment groups. Others have found similar responses to ET-1 in diabetic rat and rabbit basilar arteries (1,33). Second, because of the limited availability of ET B receptor antagonist, as well as the basilar artery segments that can be obtained from one animal, especially in the low-dose A-192621 group, we had a limited number of animals.…”
Section: ) and Magnitude (R Max ) Of Vascular Responses To Et-1 And Amentioning
confidence: 95%
See 1 more Smart Citation
“…In general support of this suggestion are the observations that (1) ET A and ET B receptors can couple to pathways predicted to either increase or decrease ET-1-induced contraction [66][67][68][69] and (2) ET-1 differentially activates the various pathways coupled to the ET A and ET B receptors depending on the ET-1 concentration. 70 It is of interest to speculate that the enhanced ET-1 contraction that occurs after ET A or ET B receptor blockade in the absence of the endothelium 7,20,22,24,37,65,71 may be due to inhibition of negative regulatory pathways. The ability of lower and higher concentrations of BQ788 to enhance and inhibit ET-1-induced contraction, respectively, 20 may also reflect ET-1 action as a biased agonist at the ET B receptor and/or BQ788 action as a biased antagonist.…”
Section: Mechanism Signaling Pathwaysmentioning
confidence: 98%
“…33 Indirect support for a role of the endothelium in the expression of cross talk may also be derived from findings in rabbit basilar artery in vitro, in which ET B receptor antagonist decreased ET-1 potency in the absence of the endothelium, whereas ET-1 potency was unaltered in the presence of the endothelium. 65 To underscore the potential influence of the endothelium/ epithelium in the expression of cross talk, the presence/ absence of the endothelium/epithelium in the various preparations demonstrating cross talk is indicated in Figure 1.…”
Section: Endothelium/epitheliummentioning
confidence: 99%